Hvordan kan miljø- og klimahensyn integreres i den økonomiske politik? - Berg, Rasmus Kehlet; Eskildsen, Janek Bligaard; Hoff, Jens Villiam; Jacobsen, Jette Bredahl; Pedersen, Ole Gravgaard; Rasmussen, Martin Møller Boje; Stephensen, Peter Philip; Sørensen, Peter Birch (Politik, 2019)
Through decades, the natural sciences have documented some troubling links between the growing economy and damages to the environment, most prominent of which are global warming and the loss of biodiversity. Recent years have however shown that the road from identifying the problems to action is slow and complicated to navigate: The goal to reduce greenhouse gas emissions does not stand alone; rather it is weighed against numerous other policy objectives. This paper first outlines a way of measuring the links between economic activity and the environment: The Green GDP. This measure attempts to measure the environmental damages in the same metric as other economic activity, thus informing us on whether or not economic growth comes at the expense of the environment. Next, the paper introduces a research project aimed at developing the GREEN REFORM model that can simulate the environmental effects of economic policy as well as the impact of environmental policy on the economy. While the Green GDP is an indication of the environmental costs of current and past economic activity, the GREEN REFORM model can be used for evaluation of future scenarios and policy interventions. Finally, the paper presents an analysis of the political barriers to adopting the above-mentioned tools in decision-making in a Danish context. The paper argues that while there is some demand for the tools, there is a potential for significant opposition in the form of political-economy constraints.